A Soluble Receptor for Advanced Glycation End Product Levels in Patients with Systemic Lupus Erythematosus - Nervana BAYOUMY,; Mohamed EL-SHABRAWI,; Hesham NADA3, (Archives of Rheumatology, 2013)
Objectives: In this study, we aimed to evaluate the plasma levels of a soluble receptor for advanced glycation end products (sRAGE) in patients with systemic lupus erythematosus (SLE) and to investigate their relationship with different clinical, laboratory, and therapeutic parameters. Patients and methods: A total of 120 patients with SLE (111 females, 9 males) and 40 age- and gender-matched healthy controls were included. The plasma sRAGE levels were measured using a commercially available enzyme-linked immunosorbent assay (ELISA). The possible relationship between plasma sRAGE levels with SLE clinical and laboratory characteristics were also assessed. The effectiveness of different therapeutic modalities on plasma sRAGE levels was analyzed. Results: The SLE patients had significantly lower plasma levels of sRAGE than the healthy controls (p=0.003). The patients with a skin rash or serositis had significantly higher sRAGE levels than those without (p=0.036 and p=0.017, respectively). The SLE patients who were treated over a longer period of time showed higher levels of sRAGE than those treated for shorter periods (p=0.000). No significant difference in levels was found among the patients treated with corticosteroids and those treated with combined therapy (p=0.89). There was a significant negative correlation between the sRAGE level and the total white blood cell (WBC) count (r=-0.356; p=0.003), lymphocytes (r=0.341; p<0.001), and neutrophils (r=-0.289; p=0.006). Conclusion: We found significantly decreased plasma sRAGE levels in the SLE patients in our study. This suggests that sRAGE levels may play a role in the pathogenesis of the disease.